2019
DOI: 10.5965/223811711812019230
|View full text |Cite
|
Sign up to set email alerts
|

Atributos do solo e produtividade do milho cultivado em sucessão a plantas de cobertura de inverno

Abstract: O objetivo deste trabalho foi avaliar o efeito de diferentes plantas de cobertura de inverno na fertilidade do solo e produtividade da cultura do milho. O experimento foi conduzido por três safras agrícolas, de 2011 a 2014. Os tratamentos utilizados foram as plantas de coberturas de inverno ervilhaca, aveia preta, tremoço azul, nabo forrageiro, azevém e ervilha forrageira cultivadas isoladamente, além dos consórcios aveia preta com ervilhaca, aveia preta com nabo forrageiro e ervilhaca, aveia preta com nabo fo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
14
0
12

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 48 publications
(29 citation statements)
references
References 34 publications
(25 reference statements)
3
14
0
12
Order By: Relevance
“…These data allow us to affirm that they are areas with limited nutrient absorption by vegetables, i.e., with reduced nutritional potential. In addition, Michelon et al, (2019) found high pH results in a carried out study evaluating the soil chemical attributes in a no-tillage system with corn for degraded area recovery.…”
Section: Resultsmentioning
confidence: 98%
“…These data allow us to affirm that they are areas with limited nutrient absorption by vegetables, i.e., with reduced nutritional potential. In addition, Michelon et al, (2019) found high pH results in a carried out study evaluating the soil chemical attributes in a no-tillage system with corn for degraded area recovery.…”
Section: Resultsmentioning
confidence: 98%
“…Moreover, the higher LOM-C and LOM-N contents found in the 0-5 cm layer in T8 indicated that the combination of soil cover plants from different families increases DM yield and, consequently, the contents of these nutrients in the soil (Michelon et al, 2019). In addition, the resulting low C/N indicates that these and other nutrients can faster be available to plants (Redin et al, 2014).…”
Section: Journal Of Agricultural Studiesmentioning
confidence: 97%
“…Sendo assim, uma alternativa viável para maximizar a qualidade da palhada formada, deixando-a mais próxima do ideal, levando em conta a rápida velocidade de degradação e da disponibilização de N pelas leguminosas e a degradação lenta e imobilização dos nutrientes pelas gramíneas. Dessa forma, é possível otimizar a liberação de N e a decomposição da palha sobre o solo, que ocorre de maneira mais lenta, mantendo o solo coberto por mais tempo favorecendo o melhor desenvolvimento das culturas (Latati et al, 2016;Michelon et al, 2019).…”
Section: De Plantas De Coberturaunclassified
“…Dentre esses fatores destacam-se a cultivar ou espécie selecionada, a taxa de semeadura e a competição entre as espécies utilizadas (Dhima et al, 2007). Os maiores rendimentos de grãos da cultura do milho foram obtidos com a utilização da combinação aveia preta + Research, Society and Development, v. 10, n. 12, e11101220008, 2021 (CC BY 4.0) | ISSN 2525-3409 | DOI: http://dx.doi.org/10.33448/rsd-v10i12.20008 ervilhaca + nabo forrageiro, do que com o cultivo solteiro dessas culturas (Michelon et al, 2019). Fialho (2020) verificou maior rendimento de grãos de soja (3762,54 kg ha -1 ) sobre a palhada de Mix de plantas de cobertura (Milheto + C. spectabilis + U. ruziziensis) em Montividiu-GO.…”
Section: De Plantas De Coberturaunclassified